The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1242/jcs.113.10.1771
|View full text |Cite
|
Sign up to set email alerts
|

Tight junctions are membrane microdomains

Abstract: Tight junctions (TJ) of polarized epithelial cells regulate barrier function at mucosal surfaces. Structural proteins of TJs include hyperphosphorylated occludin (HO) and the peripheral membrane protein, ZO-1. Since TJs are dynamically regulated, and lipid-modified signal transduction proteins localize to TJs, we considered the possibility that the TJ itself is composed of microdomains with unique structure. Differential detergent extraction and isopycnic sucrose density gradients were utilized to isolate TJ-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 398 publications
(40 citation statements)
references
References 46 publications
2
29
0
Order By: Relevance
“…Intrauterine growth restriction leads to intestinal diseases in the perinatal period and predisposes individuals to feeding intolerance and digestive diseases in the early postnatal period ( Bernstein et al., 2000 ). The movement of substances across the cell membrane depends on diffusion or active transport, which depend on the intestinal structure ( Nusrat et al., 2000 ). Consistent with our study, it has shown that intrauterine growth restriction leads to intestinal villus atrophy, mucosal oxidative damage, and intestinal dysfunction, thereby causing diarrhea and reduction in feed utilization in piglets ( Wang et al., 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…Intrauterine growth restriction leads to intestinal diseases in the perinatal period and predisposes individuals to feeding intolerance and digestive diseases in the early postnatal period ( Bernstein et al., 2000 ). The movement of substances across the cell membrane depends on diffusion or active transport, which depend on the intestinal structure ( Nusrat et al., 2000 ). Consistent with our study, it has shown that intrauterine growth restriction leads to intestinal villus atrophy, mucosal oxidative damage, and intestinal dysfunction, thereby causing diarrhea and reduction in feed utilization in piglets ( Wang et al., 2005 , 2008 ).…”
Section: Discussionmentioning
confidence: 99%
“…ZO-1 is one of the major tight junction proteins that facilitates in maintaining the BBB integrity. ZO-1 can help in predicting the healthy and pathological state of the BBB, making it a valuable marker of the endothelial barrier [ 97 ]. Decreased expression and disarrangement of ZO-1 has been associated with an increase in BBB permeability [ 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…It affects the organization of TJ proteins . Some studies demonstrate that it is also responsible for redistribution of lipid microdomain proteins like flotillin1 and caveolin1 (Nusrat et al, 2000; which are associated with TJ membrane integrity. Researchers demonstrated that Kaempferol swiftly and significantly elevated the TEER values of the Caco-2 cells, but surprisingly they did not disturbed the membrane permeability.…”
Section: Kaempferolmentioning
confidence: 99%